The effect of backroom size on retail product availability – operational and technological solutions - Nikola Milićević; Aleksandar Grubor (Amfiteatru Economic Journal, 2015)
Amid the conditions of increasingly fierce competition, retailers are doing their best to meet the demands of their customers as efficiently as possible. Through the ever-growing level of product availability they raise the quality of service, which is positively reflected not only on the growth in sales, but also customer satisfaction. In the opposite case, the out-ofstock problem emerges, affecting not only customers, but also retailers and their suppliers. Bearing in mind, that the causes of the given problem occur most frequently in the last metres of the supply chain, in this paper we investigated the effect of backroom size on product availability, depending on the retail format. For this purpose, we used moderated regression analysis on the sample of 80 fast moving consumer goods in retail stores located on the territory of the Republic of Serbia. The obtained results pointed to opposite movements in the smallest and the largest format. Whereas in superettes the out-of-stock level lowers with the increase in the backroom size, it tends to drop in hypermarkets. Therefore, we pointed to some in-store problems that cause product stock-outs in different store formats. In addition to indicating the potential causes of analyzed relations, this paper also presents certain operational and technological solutions related to their mitigation.
Keywords: M31; M30; 330; retail; product availability; backroom size; replenishment; Serbia